Isocratic RP-HPLC method for quantification of L-citrulline content in 100% watermelon [Citrullus lanatus (Thunb.) Matsum. and Nakai] juices and its role in improving swimming performance / Rasdin Ridwan - Ridwan, Rasdin (2019)
Watermelon (Citrullus lanatus (Thunb.) Matsum. and Nakai) contains high L-citrulline content that may beneficial to maximize exercise performance. The present study aimed to assess L-citrulline status in local 100% watermelon juices and investigate the role of 100% flesh and rind watermelon juices supplementation for 14 days to improve swimming performance in rats. Determination and quantification of L-citrulline in 100% flesh and rind watermelon juices were performed by isocratic RP-HPLC method on Gemini C1s using 0.1 % H3P04 as mobile phase at flow rate of 05 mL/min and detection wavelength at 195 nm. The method was validated in terms of linearity, sensitivity, accuracy and precision. L-citrulline was determined at retention time, 5.7 minutes. High concentration of L-citrulline was found in flesh and rind of 100% watermelon juices, 2.46 g/L and 3.13 g/L, respectively.